Positive electrode active material and preparation method and application thereof
By designing a positive electrode active material with a concentric hollow structure, the problem of structure collapse of the positive electrode active material under high voltage conditions is solved, and its structural stability and electrochemical properties are significantly improved.
Patent Information
- Application Number
- CN202411996765.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Under high voltage conditions, the uneven stress generated during the charge and discharge of the positive electrode active material leads to collapse of the material structure and reduces its electrochemical properties.
A positive electrode active material having a hollow structure similar to a concentric circle is designed, which includes an inner layer and an outer layer in sequence in the radial direction from the inside to the outside, the inner layer includes a third circle layer surrounding the cavity, the outer layer includes a second circle layer located on the side of the third circle layer away from the cavity, and a first circle layer located on the side of the second circle layer away from the third circle layer. By controlling the thickness of the cavity and the second ring layer, it is ensured that the material remains structurally stable under the action of stress.
It significantly improves the structural stability of the positive electrode active material, improves the first Coulomb efficiency and cycling performance, and promotes the conduction rate of lithium ions, reduces the impedance of the battery and improves the rate performance.
Smart Images

Figure CN119812306A_ABST
Abstract
Description
Technical Field
[0001] The present inventor relates to the technical field of positive electrode active materials, and in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] High voltage use is an important development direction for positive electrode active materials (such as medium-high nickel ternary materials). As the voltage increases, the amount of lithium removed from the positive electrode active material increases. During the charge and discharge process, greater uneven stress is generated inside the positive electrode active material particles, which can easily lead to microcracks in the positive electrode active material particles, causing the collapse of the positive electrode active material structure, severely damaging the structure of the positive electrode active material particles, and greatly reducing the electrochemical performance of the positive electrode active material.
[0003] Therefore, improving the structural stability during the charging and discharging process is extremely important for high-voltage polycrystalline materials. Summary of the invention
[0004] The present invention provides a positive electrode active material and a preparation method and application thereof, which are helpful to improve the structural stability of the positive electrode active material during the charging and discharging process.
[0005] The present invention provides a positive electrode active material, which includes an inner layer and an outer layer in sequence in the radial direction from the inside to the outside, the inner layer includes a third circle layer surrounding a cavity, the outer layer includes a second circle layer located on the side of the third circle layer away from the cavity, and a first circle layer located on the side of the second circle layer away from the third circle layer; the positive electrode active material is composed of primary particles, and the second circle layer is a hollow structure including the primary particles; along the radial direction from the inside to the outside, the radius of the positive electrode active material is r1, the width of the second circle layer is r2-r3, the width of the cavity is r4, the average hollow thickness of the second circle layer accounts for D1=(r2-r3) / r1, the average hollow thickness of the cavity accounts for D2=r4 / r1, and D1 and D2 satisfy 0<D1≤16%, 10%≤D2≤20%.
[0006] Optionally, the cavity does not include the primary particles.
[0007] Optionally, the change rate of D50 of the positive electrode active material after being maintained at a pressure of 3.0-3.5T for 30s is less than or equal to 5%.
[0008] Optionally, the chemical formula of the positive electrode active material is Li x Ni a Co b M c N e A fO2, wherein 0.95≤x≤1.1, 0.5≤a<1, 0≤b≤0.2, 0≤c≤0.5, a+b+c+e=1, 0<e≤0.01, 0<f≤0.01, M includes Mn and / or Al, N includes one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al, and A includes one or more of Al, W, Ti, Zr; and / or, D50 of the positive electrode active material is 10-18 μm.
[0009] The present invention provides a method for preparing a positive electrode active material as described above, comprising: 1) mixing a metal salt solution including nickel, cobalt and manganese, sodium hydroxide and ammonia water to obtain a mixed solution, wherein the pH of the mixed solution is 11.0-12.3 and the ammonia concentration is 2-15 g / L, subjecting the mixed solution to a first reaction to obtain a first mixed system, then lowering the pH of the first mixed system, increasing the ammonia concentration in the first mixed system, and conducting a second reaction to obtain a second mixed system; 2) adjusting the pH of the second mixed system to 10.5-11.5 and the ammonia concentration to 2-8 g / L, conducting a third reaction to obtain a third mixed system, then increasing the ammonia concentration in the third mixed system, and conducting a fourth reaction to obtain a hydroxide precursor; wherein the time of the first reaction is consistent with the time of the first reaction, the second reaction, the third reaction, The ratio of the time of the fourth reaction to the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4, and D3 and D4 satisfy 15%<D3≤40%, 2.5%≤D4≤15%; 3) mixing the hydroxide precursor and a raw material system including a lithium salt to obtain a mixed material; 4) performing a first sintering at 300-650°C and then cooling to 20-25°C to obtain the pre-lithiated lithium nickel cobalt manganese oxide; 5) performing a second sintering at 550-750°C for the pre-lithiated lithium nickel cobalt manganese oxide, then heating to 850-950°C for a third sintering, and then performing a fourth sintering at 780-880°C to obtain the positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
[0010] Optionally, the temperature of the first reaction is 50-75°C; and / or, the temperature of the second reaction is 50-75°C; and / or, the temperature of the third reaction is 50-75°C; and / or, the temperature of the fourth reaction is 50-75°C; and / or, in step 1), the first reaction and the second reaction are carried out under a stirring state at a rotation speed of 300rpm-500rpm; and / or, in step 2), the third reaction and the fourth reaction are carried out under a stirring state at a rotation speed of 100rpm-400rpm; the raw material system in step 3) also includes doping elements, and the doping elements include one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al; and / or, the first sintering time is 4-15h; and / or, the second sintering time is 2-4h; and / or, the third sintering time is 8-15h; and / or, the fourth sintering time is 3-5h.
[0011] Optionally, the method further includes: crushing the positive electrode active material, mixing it with a coating material, and then performing a fifth sintering at 300 to 700° C. to obtain a coated positive electrode active material, wherein the fifth sintering time is 5 to 12 hours.
[0012] Optionally, step 4) includes: heating the mixed material to 300-650°C at a rate of 1-5°C / min for a first sintering, and then cooling to 20-25°C to obtain the pre-lithiated lithium nickel cobalt manganese oxide; and / or, step 5) includes: heating the pre-lithiated lithium nickel cobalt manganese oxide to 550-750°C at a rate of 1-5°C / min for a second sintering, and then heating it to 850-950°C at a rate of 1-3°C / min for a third sintering, and then cooling it at a rate of 1-3°C / min and performing a fourth sintering at 780-880°C to obtain the positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
[0013] The present invention provides a positive electrode sheet, which comprises the positive electrode active material as described above or the positive electrode active material obtained according to the preparation method as described above.
[0014] The present invention provides a lithium ion battery, which comprises the positive electrode sheet as described above.
[0015] The present invention provides a positive electrode active material and a preparation method and application thereof. The positive electrode active material is considered to have a hollow structure similar to concentric circles, that is, a structure with a gradient hollow distribution from the inside to the outside. This hollow structure can provide a release space for the stress generated by the positive electrode active material during the charging and discharging process. At the same time, by controlling the thickness of the hollow layer (cavity and second layer) within the above range, it can be ensured that the positive electrode active material maintains structural stability under the action of stress, so that the structural stability of the positive electrode active material is significantly enhanced, thereby improving the first coulomb efficiency and cycle performance. In addition, this structure of the positive electrode active material is also conducive to the full contact between the positive electrode active material and the electrolyte, thereby improving the conduction rate of lithium ions, helping to reduce impedance, and improving rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 A schematic cross-sectional view of a positive electrode active material provided in an embodiment of the present application;
[0018] Figure 2 is a cross-sectional SEM image of the hydroxide precursor of Example 1;
[0019] Figure 3 is a cross-sectional SEM image of the positive electrode active material of Example 1;
[0020] Figure 4 This is a cross-sectional SEM image of the positive electrode active material of Comparative Example 1.
[0021] Description of reference numerals:
[0022] 10-first circle layer, 20-second circle layer, 30-third circle layer, 40-cavity, 1-circle 1, 2-circle 2, 3-circle 3, 4-circle 4. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0024] In the prior art, during the charge and discharge process, greater uneven stress is generated inside the positive electrode active material particles, which easily leads to microcracks in the positive electrode active material particles, causing the collapse of the positive electrode active material structure, seriously damaging the structure of the positive electrode active material particles, and greatly reducing the electrochemical performance of the positive electrode active material.
[0025] In order to overcome the defects in the prior art, an embodiment of the present invention provides a positive electrode active material, which includes an inner layer and an outer layer in sequence in the radial direction from the inside to the outside, the inner layer includes a third circle layer enclosing a cavity, and the outer layer includes a second circle layer located on the side of the third circle layer away from the cavity, and a first circle layer located on the side of the second circle layer away from the third circle layer; the positive electrode active material is composed of primary particles, and the second circle layer is a hollow structure including primary particles; along the radial direction from the inside to the outside, the radius of the positive electrode active material is r1, the width of the second circle layer is r2-r3, the width of the cavity is r4, the average hollow thickness of the second circle layer accounts for D1=(r2-r3) / r1, the average hollow thickness of the cavity accounts for D2=r4 / r1, D1 and D2 satisfy 0<D1≤16%, 10%≤D2≤20%.
[0026] According to the inventor's research and analysis: Figure 1 As shown, the positive electrode active material includes, in the radial direction from the inside to the outside, a cavity (40), a third layer (30) surrounding the cavity (40), a second layer (20) located on the side of the third layer (30) away from the cavity (40), and a first layer (10) located on the side of the second layer (20) away from the third layer (30), wherein the positive electrode active material is composed of primary particles, and the second layer (20) is a hollow structure including primary particles; the cavity (40) and the second layer (20) can be used as hollow structure areas in the positive electrode active material, so the positive electrode active material can be regarded as having a hollow structure similar to concentric circles. The hollow structure has a gradient hollow distribution from the inside to the outside. This hollow structure can provide a release space for the stress generated by the positive electrode active material during the charge and discharge process. At the same time, by controlling the thickness of the hollow layer (cavity (40) and the second layer (20)) within the above range, it can ensure that the positive electrode active material maintains structural stability under the action of stress, so that the structural stability of the positive electrode active material is significantly enhanced, thereby improving the initial coulombic efficiency and cycle performance. In addition, this structure of the positive electrode active material is also conducive to the full contact between the positive electrode active material and the electrolyte, improving the conduction rate of lithium ions, helping to reduce impedance and improve rate performance.
[0027] Therefore, the positive electrode active material of the embodiment of the present invention has strong structural stability and can maintain high structural stability during the charge and discharge process, which helps to improve the initial coulombic efficiency and cycle performance of the battery. In addition, the lithium ion conduction rate of the above-mentioned positive electrode active material is high, which helps to reduce impedance and improve rate performance.
[0028] The positive electrode active material of the embodiment of the present invention can be a quasi-spherical or round particle, such as Figure 1 As shown, circle 1 (1) is located in the outer edge layer of the first circle layer (10), circle 2 (2) is located in the outer edge layer of the second circle layer (20), circle 3 (3) is located in the outer edge layer of the third circle layer (30), and circle 4 (4) is located in the outer edge layer of the cavity (40). The corresponding diameters of circle 1, circle 2, circle 3 and circle 4 are d1, d2, d3 and d4 respectively. The average hollow thickness ratio D1 of the second circle layer can also be expressed as (d2-d3) / d1, and the average hollow thickness ratio D2 of the cavity can also be expressed as d4 / d1.
[0029] Exemplarily, the average hollow thickness proportion D1 of the second circle layer may be 1%, 5%, 10%, 15%, 16% or a range consisting of any two thereof.
[0030] Exemplarily, the average hollow thickness proportion D2 of the cavity may be 10%, 12%, 14%, 16%, 18%, 20% or a range consisting of any two thereof.
[0031] The positive electrode active material may be composed of primary particles.
[0032] In some embodiments, the cavity in the inner layer of the positive electrode active material does not include primary particles, that is, the cavity is a hollow structure, which helps to provide a release space for the stress generated by the positive electrode active material during the charge and discharge process, thereby improving the structural stability of the positive electrode active material.
[0033] In some embodiments, the second outer layer of the positive electrode active material comprises primary particles, that is, Figure 1 The second circle layer (20) between the circle 2 and the circle 3 shown contains a connecting pillar for connecting the first circle layer (10) and the third circle layer (30), which can provide stress release space, improve the transmission efficiency of lithium ions, and maintain the stability of the positive electrode active material structure.
[0034] Furthermore, in some embodiments, it can be seen from the cross-sectional view of the positive electrode active material particles that the pillar structure in the second layer (hollow layer) divides the second layer (hollow layer) into a plurality of chambers, and the number of chambers is n, where n ≥ 1, which can improve the stress resistance of the positive electrode active material and thereby improve its structural stability.
[0035] After the positive electrode active material is kept at a pressure of 3.0 to 3.5 T for 30 seconds, the change rate (ΔD50) of D50 (median particle size) is less than or equal to 5%, indicating that the positive electrode active material of the embodiment of the present invention still has good particle strength even if the structure is hollow.
[0036] The above D50 change rate (ΔD50) = (D50 压前 -D50 压后 ) / D50 压前 , that is, first calculate the D50 (D50 压前 ) and D50 (D50 压后 ), and then calculate the difference between the above difference and D50 压前 The ratio of D50 to D50 is obtained.
[0037] In some embodiments, the D50 of the positive electrode active material is 10-18 μm. Within the above D50 range, the positive electrode active material has better structural stability.
[0038] The above-mentioned positive electrode material can be a polycrystalline ternary positive electrode material.
[0039] In some embodiments, the chemical formula of the positive electrode material is Li x Ni a Co b M c N e A f O2, wherein 0.95≤x≤1.1, 0.5≤a<1, 0≤b≤0.2, 0≤c≤0.5, a+b+c+e=1, 0<e≤0.01, 0<f≤0.01, M includes Mn and / or Al, N includes one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al, and A includes one or more of Al, W, Ti, Zr.
[0040] The embodiment of the present invention also provides a method for preparing the above-mentioned positive electrode active material, comprising: 1) mixing a metal salt solution including nickel, cobalt, and manganese, sodium hydroxide, and ammonia water to obtain a mixed solution, wherein the pH of the mixed solution is 11.0 to 12.3 and the ammonia concentration is 2 to 15 g / L, subjecting the mixed solution to a first reaction to obtain a first mixed system, then lowering the pH of the first mixed system, increasing the ammonia concentration in the first mixed system, and conducting a second reaction to obtain a second mixed system; 2) adjusting the pH of the second mixed system to 10.5 to 11.5 and the ammonia concentration to 2 to 8 g / L, conducting a third reaction to obtain a third mixed system, then increasing the ammonia concentration in the third mixed system, and conducting a fourth reaction to obtain a hydroxide precursor; wherein the time of the first reaction is the same as the time of the first reaction and the second reaction. The ratio of the time of the third reaction to the time of the first reaction, the second reaction, the third reaction and the fourth reaction is D3, the ratio of the time of the third reaction to the time of the first reaction, the second reaction, the third reaction and the fourth reaction is D4, D3 and D4 satisfy 15%<D3≤40%, 2.5%≤D4≤15%; 3) mixing a hydroxide precursor and a raw material system including a lithium salt to obtain a mixed material; 4) performing a first sintering on the mixed material at 300-650°C, and then cooling to 20-25°C to obtain a pre-lithiated lithium nickel cobalt manganese oxide; 5) performing a second sintering on the pre-lithiated lithium nickel cobalt manganese oxide at 550-750°C, and then heating to 850-950°C for a third sintering, and then performing a fourth sintering at 780-880°C to obtain a positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
[0041] The overall steps 1) and 2) in the above preparation method can be understood as a process for preparing a hydroxide precursor by precipitation method, which is specifically divided into step 1) - nucleation stage, step 2) - growth stage; the overall steps 3), 4) and 5) can be understood as a process for preparing a positive electrode active material by using the above hydroxide precursor.
[0042] In the nucleation stage, sodium hydroxide is used as a precipitant and ammonia water is used as a complexing agent. The pH of the mixed solution is controlled to 11.0-12.3 and the ammonia concentration is controlled to 2g / L-15g / L by adjusting the flow of sodium hydroxide and ammonia water, and then the first reaction is carried out. After the first reaction is completed, the pH of the first mixed system is reduced and the ammonia concentration in the first mixed system is increased to carry out the second reaction. By adjusting the pH of the second reaction stage to be lower than the pH of the first reaction stage and the ammonia concentration of the second reaction stage to be higher than the ammonia concentration of the first reaction stage, an inner layer structure (the core of the precursor) with loose inside and dense outside can be formed, laying a good foundation for forming the structure of the above-mentioned positive electrode active material.
[0043] Illustratively, the pH in the nucleation stage can be 11.0, 11.5, 12.0, 12.3, or a range consisting of any two thereof, and the ammonia concentration can be 2 g / L, 5 g / L, 10 g / L, 15 g / L, or a range consisting of any two thereof.
[0044] In the growth stage, the pH of the second mixed system is controlled to 10.5-11.5 and the ammonia concentration is 2-8 g / L by adjusting the flow of sodium hydroxide and ammonia water, and the third reaction is carried out. After the third reaction is completed, the ammonia concentration in the third mixed system is increased to carry out the fourth reaction. By adjusting the ammonia concentration in the fourth reaction stage to be higher than the ammonia concentration in the third reaction stage, an outer layer structure with loose interior and dense exterior can be grown on the outer layer of the above inner layer structure, laying a good foundation for forming the structure of the above positive electrode active material.
[0045] Illustratively, the pH in the growth stage can be 10.5, 11.0, 11.5, or a range consisting of any two thereof, and the ammonia concentration can be 2 g / L, 5 g / L, 6 g / L, 8 g / L, or a range consisting of any two thereof.
[0046] By controlling the time of the first reaction and the third reaction to meet the following conditions: 15%<D3≤40%, 2.5%≤D4≤15%, it helps to form a positive electrode active material whose cavity and the thickness of the second layer meet the following conditions: 0<D1≤16%, 10%≤D2≤20%.
[0047] By controlling the precipitation reaction process of the above steps 1) and 2), a nickel-cobalt-manganese hydroxide precursor with a specific structure (the inner core is tight outside and loose inside, and it is loose at first and then compact during the growth stage) is obtained, which is conducive to the formation of a positive electrode active material with a specific hollow structure during the sintering process.
[0048] In step 3), the hydroxide precursor and the raw material system including the lithium salt are fully mixed to obtain a mixed material.
[0049] In step 4), the mixed material is first sintered at 300-650° C., and then cooled to 20-25° C. to obtain pre-lithiated lithium nickel cobalt manganese oxide. Exemplarily, the temperature of the first sintering can be 300° C., 400° C., 500° C., 600° C., 650° C., or a range consisting of any two thereof.
[0050] After the first sintering is completed, the material can be cooled by natural cooling to room temperature, for example, 20-25° C., to obtain pre-lithiated lithium nickel cobalt manganese oxide.
[0051] In step 5), the pre-lithiated lithium nickel cobalt manganese oxide (secondary sphere) is subjected to a second sintering at 550-750°C, then heated to 850-950°C for a third sintering, and then subjected to a fourth sintering at 780-880°C to obtain a positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering. In step 5), the sintering temperature (insulation platform temperature) is controlled to control the diffusion rate of the lithium salt inside the pre-lithiated lithium nickel cobalt manganese oxide (secondary sphere), so that the lithium salt is deposited in an orderly manner inside the precursor, and in-situ growth is achieved during the sintering process (high temperature section), forming a positive electrode active material having both an inner layer (inner ring layer) and an outer layer (outer ring layer) hollow structure.
[0052] Illustratively, the temperature of the second sintering may be 550°C, 600°C, 650°C, 700°C, 750°C or a range consisting of any two thereof, the temperature of the third sintering may be 850°C, 900°C, 950°C or a range consisting of any two thereof, and the temperature of the fourth sintering may be 780°C, 800°C, 850°C, 880°C or a range consisting of any two thereof.
[0053] The above-mentioned preparation method can be used to prepare a positive electrode active material having the aforementioned concentric circle-like hollow structure. The positive electrode active material has strong structural stability, which helps to improve the initial coulombic efficiency and cycle performance of the battery. In addition, the positive electrode active material has a high lithium ion conduction rate, which helps to reduce impedance and improve rate performance.
[0054] The embodiment of the present invention is not limited to providing the raw materials of nickel, cobalt and manganese in the metal salt solution including nickel, cobalt and manganese. For example, nickel sulfate, cobalt sulfate and manganese sulfate can be used as raw materials.
[0055] In some embodiments, a metal salt solution (mixed metal salt solution) including nickel, cobalt, and manganese can be prepared by the following process: water (eg, pure water) is used as a solvent and nickel sulfate, cobalt sulfate, and manganese sulfate are used as raw materials.
[0056] In step 1), a metal salt solution (mixed metal salt solution) including nickel, cobalt and manganese, a NaOH solution and an ammonia solution can also be added into the reaction kettle simultaneously through a mass flow meter.
[0057] Generally, in the nucleation stage, the feed rate of the mixed metal salt solution can be controlled to be 70-90 mL / min, such as 70 mL / min, 80 mL / min, 90 mL / min or any two thereof.
[0058] The temperature of the first reaction may be 50-75°C; and / or, the temperature of the second reaction may be 50-75°C; and / or, the temperature of the third reaction may be 50-75°C; and / or, the temperature of the fourth reaction may be 50-75°C. By controlling the temperatures of the first reaction, the second reaction, the third reaction, and the fourth reaction to conform to the above ranges, it is helpful to avoid abnormalities in morphology, primary particles, structure, etc. during the precursor synthesis process, and further ensure that the positive electrode material having a similar concentric hollow structure of the embodiment of the present invention can be synthesized.
[0059] In addition, in step 1), the first reaction and the second reaction can be carried out under stirring at a speed of 300 rpm to 500 rpm. It is helpful to improve the above structure of the positive electrode active material, improve its structural stability and lithium ion conductivity, and thus improve the first coulomb efficiency, cycle performance, rate performance of the battery, and reduce impedance. Exemplarily, the above speed can be 300 rpm, 400 rpm, 500 rpm, or a range consisting of any two of them.
[0060] In step 2), the third reaction and the fourth reaction can be carried out under stirring at a speed of 100 rpm to 400 rpm. It is helpful to improve the above structure of the positive electrode active material, improve its structural stability and lithium ion conductivity, and thus improve the first coulomb efficiency, cycle performance, rate performance of the battery, and reduce impedance. Exemplarily, the above speed can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm or a range consisting of any two of them.
[0061] Generally, during the growth stage, the feed rate of the mixed metal salt solution can be controlled to be 90-110 mL / min, such as 90 mL / min, 100 mL / min, 110 mL / min or a range consisting of any two thereof.
[0062] The lithium salt in step 3) may include a lithium salt with a low melting point, for example, may include one or more of lithium hydroxide, lithium nitrate, and lithium acetate.
[0063] In addition, the raw material system in step 3) may further include a doping element (dopant), which may include one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al. After adding the above doping elements, a lithium nickel cobalt manganese metal oxide positive electrode active material containing element doping can be obtained, further improving the stability of the positive electrode active material.
[0064] Step 4) also includes: heating the mixed material to 300-650°C at a rate of 1-5°C / min for a first sintering, and then cooling to 20-25°C to obtain pre-lithiated lithium nickel cobalt manganese oxide. Limiting the heating rate within the above range helps to improve the above structure of the positive electrode active material, improve its structural stability and lithium ion conductivity, and thus improve the first coulombic efficiency, cycle performance, rate performance of the battery, and reduce impedance. Exemplarily, the above heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range consisting of any two of them.
[0065] In addition, the first sintering time (holding time) may be 4 to 15 h, for example, 4 h, 5 h, 6 h, 10 h, 11 h, 14 h, 15 h or a range consisting of any two of them.
[0066] Step 5) also includes: heating the pre-lithiated lithium nickel cobalt manganese oxide to 550-750°C at a rate of 1-5°C / min for a second sintering, then heating it to 850-950°C at a rate of 1-3°C / min for a third sintering, then cooling it at a rate of 1-3°C / min, and performing a fourth sintering at 780-880°C to obtain a positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
[0067] After the fourth sintering is completed, the material can be naturally cooled to room temperature to obtain the positive electrode active material.
[0068] In addition, the second sintering time (holding time) can be 2 to 4 hours, such as 2 hours, 3 hours, 4 hours or any two of them, the third sintering time (holding time) can be 8 to 15 hours, such as 8 hours, 10 hours, 12 hours, 14 hours, 15 hours or any two of them, and the fourth sintering time (holding time) can be 3 to 5 hours, such as 3 hours, 4 hours, 5 hours or any two of them. While controlling the sintering temperature (holding platform temperature), the holding time is controlled within the above corresponding range, and the diffusion rate of the lithium salt in the pre-lithiated lithium nickel cobalt manganese oxide (secondary ball) can be controlled, so that the lithium salt is deposited in an orderly manner inside the precursor, and in-situ growth is achieved during the sintering process (high temperature section), forming a positive electrode active material having both an inner layer (inner ring layer) and an outer layer (outer ring layer) hollow structure.
[0069] The first sintering, the second sintering, the third sintering, the fourth sintering and the fifth sintering of the embodiment of the present invention can all be performed under an oxygen or air atmosphere.
[0070] In some embodiments, the preparation method further comprises: crushing the positive electrode active material (crushing treatment), then mixing it with the coating material, and then performing a fifth sintering at 300-700°C to obtain a coated positive electrode active material, wherein the fifth sintering time (heat preservation time) is 5-12 hours. A coating layer of a certain thickness is formed on the surface and inside of the positive electrode active material, so that the stability of the bulk phase and the inner and outer surfaces is improved.
[0071] Furthermore, during the fifth sintering process, the mixed material may be heated to 300-700° C. at a rate of 1-10° C. / min for the fifth sintering.
[0072] It is understandable that after the fifth sintering is completed, the sintered material can be naturally cooled to room temperature and then sieved to obtain the positive electrode active material.
[0073] In some embodiments, a positive electrode active material having a certain hollow structure is obtained by high-temperature solid-phase sintering using the aforementioned special structured hydroxide precursor and a low-melting-point lithium salt, and the hollow structure is similar to concentric circles. In addition, bulk doping and surface coating (such as wet coating) are performed to form a coating layer of a certain thickness on the surface and inside of the positive electrode active material, thereby protecting the internal structure and internal and external interfaces of the positive electrode active material, thereby improving the stability of the bulk phase and the internal and external surfaces, which can not only accelerate the transmission efficiency of lithium ions, but also maintain the integrity of the structure of the positive electrode active material during long-term cycles.
[0074] Based on the same inventive concept, an embodiment of the present invention further provides a positive electrode sheet, which includes the positive electrode active material mentioned above or the positive electrode active material obtained according to the above preparation method.
[0075] The positive electrode sheet of the embodiment of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed of the positive electrode active material and arranged on the surface of the positive electrode current collector.
[0076] When preparing the positive electrode sheet, for example, the positive electrode active material of the present invention, the conductive agent and the binder are dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and the mixture is stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and cutting. For example, the positive electrode active layer includes 70-99wt% of the positive electrode active material, 0.5-15wt% of the conductive agent, and 0.5-15wt% of the binder according to the mass percentage, and further includes 80-98wt% of the positive electrode active material, 1-10wt% of the conductive agent, and 1-10wt% of the binder.
[0077] The material of the above-mentioned positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.
[0078] The battery prepared using the positive electrode sheet has excellent coulombic efficiency, cycle performance, rate performance and low impedance.
[0079] Based on the same inventive concept, an embodiment of the present invention provides a lithium-ion battery, which includes the above-mentioned positive electrode sheet. It is conceivable that the lithium-ion battery of the embodiment of the present invention includes a negative electrode sheet, an electrolyte and a separator in addition to the above-mentioned positive electrode sheet.
[0080] The embodiments of the present invention do not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.
[0081] The embodiments of the present invention do not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in the current lithium-ion battery electrolyte, and the electrolyte lithium salts commonly used in the current lithium-ion electrolyte, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, cyclopentane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0082] The embodiments of the present invention do not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, and a diaphragm with a ceramic coating.
[0083] When preparing lithium-ion batteries, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the lithium-ion battery. The lithium-ion battery has excellent coulomb efficiency, cycle performance, rate performance and low impedance.
[0084] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0085] Example 1
[0086] This embodiment provides a method for preparing a positive electrode active material, comprising:
[0087] 1) Using pure water as solvent, nickel sulfate, cobalt sulfate and manganese sulfate as raw materials, according to Ni 2+ :Co 2+ :Mn 2+ (molar ratio) = 6:2:2, prepare a metal salt solution (mixed metal salt solution) including nickel, cobalt and manganese with a metal ion concentration of 2 mol / L, and prepare a NaOH solution with a NaOH concentration of 2 mol / L and an ammonia solution with an ammonia concentration of 4.3 mol / L; add the mixed metal salt solution, NaOH solution and ammonia solution into the reactor through a mass flow meter to mix them to obtain a mixed solution, control the feed rate of the mixed metal salt solution to 80 mL / min, control the pH of the mixed solution to 11.8 and the ammonia concentration to 2.5 g / L by adjusting the flow rates of sodium hydroxide and ammonia water, and make the mixed solution undergo a first reaction to obtain a first mixed system, and after the first reaction is carried out for 30 hours, adjust the pH of the first mixed system to 11.6 and the ammonia concentration to 3.5 g / L, and carry out a second reaction, the time of the second reaction is 30 hours, and a second mixed system is obtained; wherein, the first reaction and the second reaction are carried out at a rotation speed of 400 rpm and a temperature of 55°C;
[0088] 2) The feed rate of the mixed metal salt solution was adjusted to 100 mL / min, and the pH of the second mixed system was adjusted to 10.8 and the ammonia concentration was adjusted to 3 g / L, and a third reaction was performed to obtain a third mixed system. After the third reaction was performed for 10 hours, the pH of the third mixed system was increased to 10.9 and the ammonia concentration was increased to 4 g / L, and a fourth reaction was performed. The fourth reaction time was 40 hours, and a hydroxide precursor (Ni 0.6 Co 0.2 Mn 0.2(OH)2 precursor); wherein the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3 = 27.27%, the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4 = 9.09%, and the third reaction and the fourth reaction are carried out at a rotation speed of 200 rpm and a temperature of 55 ° C.;
[0089] 3) uniformly mixing the hydroxide precursor, lithium hydroxide and zirconium oxide in a molar ratio of 1:1.08:0.002 to obtain a mixed material;
[0090] 4) In an oxygen atmosphere, the mixture is heated to 500° C. at a rate of 3° C. / min for a first sintering, the temperature is kept at this temperature for 8 hours, and then cooled to room temperature to obtain a pre-lithiated lithium nickel cobalt manganese oxide;
[0091] 5) In an oxygen atmosphere, the pre-lithiated lithium nickel cobalt manganese oxide is heated to 600° C. at a rate of 3° C. / min for a second sintering, the heat preservation time is 3 hours, and then the temperature is increased to 900° C. at a rate of 2° C. / min for a third sintering, the heat preservation time is 10 hours, and then the temperature is reduced to 800° C. at a rate of 2° C. / min for a fourth sintering, the heat preservation time is 4 hours, and then naturally cooled to room temperature to obtain a positive electrode active material (doped modified positive electrode active material);
[0092] 6) The positive electrode active material is crushed, and then the crushed positive electrode active material and alumina are mixed at a molar ratio of 1:0.0005. After mixing evenly, the mixture is heated to 550°C at 3°C / min in an oxygen atmosphere for the fifth sintering. After keeping the temperature for 8 hours, it is naturally cooled to room temperature and then sieved to obtain a positive electrode active material with a hollow structure.
[0093] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 is 10%, the average hollow thickness of the cavity accounts for D2 is 13%, and after applying a pressure of 3.5T, ΔD50 is 2.38%.
[0094] Example 2
[0095] This embodiment is basically the same as Embodiment 1, except that:
[0096] The time for the first reaction is 42 hours, the time for the second reaction is 18 hours, the time for the third reaction is 10 hours, and the time for the fourth reaction is 50 hours. That is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=35%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=8.33%; other conditions remain unchanged.
[0097] After testing, the particle size of the hydroxide precursor of Example 2 is 16.5μm, the D50 of the positive electrode active material is 16.0μm, the average hollow thickness of the second layer accounts for D1 of 6%, the average hollow thickness of the cavity accounts for D2 of 17%, and after applying a pressure of 3.5T, ΔD50 is 3.84%.
[0098] Example 3
[0099] This embodiment is basically the same as Embodiment 1, except that:
[0100] In step 1), the pH of the mixed solution is 11.3 and the ammonia concentration is 2 g / L. After the first reaction is completed, the pH of the first mixed system is adjusted to 11 and the ammonia concentration is adjusted to 3 g / L;
[0101] In step 2), the pH of the second mixed system is 11.5 and the ammonia concentration is 6 g / L. After the third reaction is completed, the ammonia concentration of the third mixed system is adjusted to 8 g / L; other conditions remain unchanged.
[0102] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for 7.5% of D1, the average hollow thickness of the cavity accounts for 10.6% of D2, and after applying a pressure of 3.5T, ΔD50 is 1.02%.
[0103] Example 4
[0104] This embodiment is basically the same as Embodiment 1, except that:
[0105] In step 1), the pH of the mixed solution is 12.3 and the ammonia concentration is 14 g / L. The pH of the first mixed system is adjusted to 12.2 and the ammonia concentration is adjusted to 15 g / L.
[0106] In step 2), the pH of the second mixed system is 10.5 and the ammonia concentration is 2 g / L. After the third reaction is completed, the ammonia concentration of the third mixed system is adjusted to 3 g / L; other conditions remain unchanged.
[0107] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for 14.7% of D1, the average hollow thickness of the cavity accounts for 18.4% of D2, and after applying a pressure of 3.5T, ΔD50 is 4.31%.
[0108] Example 5
[0109] This embodiment is basically the same as Embodiment 1, except that:
[0110] The time for the first reaction is 16.5 h, the time for the second reaction is 43.5 h, the time for the third reaction is 16.5 h, and the time for the fourth reaction is 33.5 h. That is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=15%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=15%; other conditions remain unchanged.
[0111] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 is 15.3%, the average hollow thickness of the cavity accounts for D2 is 11.2%, and after applying a pressure of 3.5T, ΔD50 is 3.31%.
[0112] Example 6
[0113] This embodiment is basically the same as Embodiment 1, except that:
[0114] The time of the first reaction is 44h, the time of the second reaction is 16h, the time of the third reaction is 3h, and the time of the fourth reaction is 47h. That is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=40%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=2.7%; other conditions remain unchanged.
[0115] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 is 2.8%, the average hollow thickness of the cavity accounts for D2 is 19.6%, and after applying a pressure of 3.5T, ΔD50 is 2.89%.
[0116] Example 7
[0117] This embodiment is basically the same as Embodiment 1, except that:
[0118] Step 4) comprises: heating the mixture to 300° C. at a rate of 1° C. / min in an air atmosphere for a first sintering, keeping the temperature for 15 hours, and then cooling to room temperature to obtain a pre-lithiated lithium nickel cobalt manganese oxide;
[0119] Step 5) comprises: in an air atmosphere, heating the pre-lithiated lithium nickel cobalt manganese oxide to 550° C. at a rate of 1° C. / min for a second sintering, holding the temperature for 4 hours, then heating the pre-lithiated lithium nickel cobalt manganese oxide to 950° C. at a rate of 3° C. / min for a third sintering, holding the temperature for 8 hours, then cooling the pre-lithiated lithium nickel cobalt manganese oxide to 880° C. at a rate of 1° C. / min for a fourth sintering, holding the temperature for 3 hours, and then naturally cooling the pre-lithiated lithium nickel cobalt manganese oxide to room temperature to obtain a positive electrode active material (doped modified positive electrode active material);
[0120] Step 6) comprises: crushing the above-mentioned positive electrode active material, and then mixing the crushed positive electrode active material and alumina in a molar ratio of 1:0.0005. After mixing evenly, in an oxygen atmosphere, heating the mixture to 700°C at 10°C / min for the fifth sintering, keeping the temperature for 5 hours, naturally cooling to room temperature, and then sieving to obtain a positive electrode active material with a hollow structure.
[0121] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for 8.95% of D1, the average hollow thickness of the cavity accounts for 11.69% of D2, and after applying a pressure of 3.5T, ΔD50 is 3.78%.
[0122] Example 8
[0123] This embodiment is basically the same as Embodiment 1, except that:
[0124] Step 4) comprises: in an air atmosphere, heating the mixed material to 650° C. at a rate of 5° C. / min for a first sintering, holding the temperature for 4 hours, and then cooling to room temperature to obtain a pre-lithiated lithium nickel cobalt manganese oxide;
[0125] Step 5) comprises: in an air atmosphere, heating the pre-lithiated lithium nickel cobalt manganese oxide to 750° C. at a rate of 5° C. / min for a second sintering, holding the temperature for 2 hours, then heating the pre-lithiated lithium nickel cobalt manganese oxide to 850° C. at a rate of 1° C. / min for a third sintering, holding the temperature for 15 hours, then cooling the pre-lithiated lithium nickel cobalt manganese oxide to 780° C. at a rate of 3° C. / min for a fourth sintering, holding the temperature for 5 hours, and then naturally cooling the pre-lithiated lithium nickel cobalt manganese oxide to room temperature to obtain a positive electrode active material (doped modified positive electrode active material);
[0126] 6) The positive electrode active material is crushed, and then the crushed positive electrode active material and alumina are mixed at a molar ratio of 1:0.0005. After mixing evenly, the mixture is heated to 300°C at 1°C / min in an oxygen atmosphere for the fifth sintering. After keeping the temperature for 12 hours, it is naturally cooled to room temperature and then sieved to obtain a positive electrode active material with a hollow structure.
[0127] After testing, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 is 12.42%, the average hollow thickness of the cavity accounts for D2 is 15.43%, and after applying a pressure of 3.5T, ΔD50 is 1.88%.
[0128] Example 9
[0129] This embodiment is basically the same as Embodiment 1, except that:
[0130] Step 1) The time of the first reaction is 36h, the time of the second reaction is 29h, the time of the third reaction is 8h, and the time of the fourth reaction is 57h, that is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=27.69%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=6.15%; other conditions remain unchanged.
[0131] After testing, the particle size of the hydroxide precursor of Example 9 is 18.5μm, the D50 of the positive electrode active material is 16.0μm, the average hollow thickness of the second layer accounts for D1 of 8.73%, the average hollow thickness of the cavity accounts for D2 of 12.24%, and after applying a pressure of 3.5T, ΔD50 is 2.73%.
[0132] Example 10
[0133] This embodiment is basically the same as Embodiment 1, except that:
[0134] Step 1) The time of the first reaction is 27h, the time of the second reaction is 28h, the time of the third reaction is 8h, and the time of the fourth reaction is 37h, that is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=27%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=8%; other conditions remain unchanged.
[0135] After testing, the particle size of the hydroxide precursor of Example 10 is 10.5μm, the D50 of the positive electrode active material is 10.0μm, the average hollow thickness of the second layer accounts for D1 of 9.86%, the average hollow thickness of the cavity accounts for D2 of 15.73%, and after applying a pressure of 3.5T, ΔD50 is 1.86%.
[0136] Embodiment 11
[0137] This embodiment is basically the same as Embodiment 1, except that:
[0138] Step 1) Adjust Ni 2+ :Co 2+ :Mn 2+ (molar ratio) = 5:2:3, and a hydroxide precursor (Ni 0.5 Co 0.2 Mn 0.3 (OH)2 precursor); other conditions remain unchanged.
[0139] After testing, the particle size of the hydroxide precursor of Example 11 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 8.46%, the average hollow thickness of the cavity accounts for D2 of 12.73%, and after applying a pressure of 3.5T, ΔD50 is 1.77%.
[0140] Example 12
[0141] This embodiment is basically the same as Embodiment 1, except that:
[0142] Step 1) Adjust Ni 2+ :Co 2+ :Mn 2+ (molar ratio) = 9:0.5:0.5, and a hydroxide precursor (Ni 0.9 Co 0.05 Mn 0.05 (OH)2 precursor), and other conditions remained unchanged.
[0143] After testing, the particle size of the hydroxide precursor of Example 12 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 11.26%, the average hollow thickness of the cavity accounts for D2 of 14.77%, and after applying a pressure of 3.5T, ΔD50 is 2.63%.
[0144] Example 13
[0145] This embodiment is basically the same as Embodiment 1, except that:
[0146] In step 3), zirconium oxide is replaced by titanium dioxide, and other conditions remain unchanged.
[0147] Embodiment 14
[0148] Step 6) Replace aluminum oxide with tungsten oxide, and keep other conditions unchanged.
[0149] Comparative Example 1
[0150] This comparative example is basically the same as Example 1, except that:
[0151] Step 2) includes adjusting the feed rate of the mixed metal salt solution to 100 mL / min, adjusting the pH of the second mixed system to 10.8 and the ammonia concentration to 10 g / L, and performing a third reaction for 50 h to obtain a hydroxide precursor (Ni 0.6 Co 0.2 Mn 0.2 (OH)2 precursor);
[0152] Step 4) and step 5) include: in an oxygen atmosphere, heating the above-mentioned mixed material to 900°C at a rate of 3°C / min for a first sintering, keeping the temperature for 10 hours, and then naturally cooling to room temperature to obtain a positive electrode active material (doped modified positive electrode active material); other conditions remain unchanged.
[0153] After testing, the particle size of the hydroxide precursor of Comparative Example 1 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 0%, the average hollow thickness of the cavity accounts for D2 of 21.2%, and after applying a pressure of 3.5T, ΔD50 is 6.93%.
[0154] Comparative Example 2
[0155] This comparative example is basically the same as Example 1, except that:
[0156] Step 1) comprises: using pure water as solvent, nickel sulfate, cobalt sulfate and manganese sulfate as raw materials, and mixing according to Ni 2+ :Co 2+ :Mn 2+ (molar ratio) = 6:2:2, prepare a metal salt solution (mixed metal salt solution) including nickel, cobalt and manganese with a metal ion concentration of 2 mol / L, and prepare a NaOH solution with a NaOH concentration of 2 mol / L and an ammonia solution with an ammonia concentration of 4.3 mol / L; add the mixed metal salt solution, NaOH solution and ammonia solution into the reactor through a mass flow meter for mixing to obtain a mixed solution, control the feed rate of the mixed metal salt solution to 80 mL / min, control the pH of the mixed solution to 11.8 and the ammonia concentration to 3.5 g / L by adjusting the flow rates of sodium hydroxide and ammonia water, and make the mixed solution undergo a first reaction, and the first reaction time is 60 h; wherein, the above-mentioned first reaction is carried out at a rotation speed of 400 rpm and a temperature of 55°C; obtain a first reaction system; then make the first reaction system react according to steps 2) to 6) in Example 1 to obtain a positive electrode active material.
[0157] After testing, the particle size of the hydroxide precursor of Comparative Example 2 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 9.3%, the average hollow thickness of the cavity accounts for D2 of 4.7%, and after applying a pressure of 3.5T, ΔD50 is 2.15%.
[0158] Comparative Example 3
[0159] This comparative example is basically the same as Example 1, except that:
[0160] Step 1) comprises: using pure water as solvent, nickel sulfate, cobalt sulfate and manganese sulfate as raw materials, and mixing according to Ni2+ :Co 2+ :Mn 2+ (molar ratio) = 6:2:2, prepare a metal salt solution (mixed metal salt solution) including nickel, cobalt and manganese with a metal ion concentration of 2 mol / L, and prepare a NaOH solution with a NaOH concentration of 2 mol / L and an ammonia solution with an ammonia concentration of 4.3 mol / L; add the mixed metal salt solution, NaOH solution and ammonia solution into the reactor through a mass flow meter to mix them to obtain a mixed solution, control the feed rate of the mixed metal salt solution to 80 mL / min, control the pH of the mixed solution to 11.3 and the ammonia concentration to 3.5 g / L by adjusting the flow rates of sodium hydroxide and ammonia water, and make the mixed solution undergo a first reaction, and the first reaction time is 60 h; wherein, the first reaction is carried out at a rotation speed of 400 rpm and a temperature of 55° C.; obtain a first reaction system;
[0161] Step 2) includes adjusting the feed rate of the mixed metal salt solution to 100 mL / min, adjusting the pH of the second mixed system to 10.8 and the ammonia concentration to 10 g / L, and performing a third reaction for 50 h to obtain a hydroxide precursor (Ni 0.6 Co 0.2 Mn 0.2 (OH)2 precursor); other conditions remain unchanged.
[0162] After testing, the particle size of the hydroxide precursor of Comparative Example 3 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 0%, the average hollow thickness of the cavity accounts for D2 of 0.76%, and after applying a pressure of 3.5T, ΔD50 is 0.97%.
[0163] Comparative Example 4
[0164] This comparative example is basically the same as Example 1, except that:
[0165] The time of the first reaction is 30h, the time of the second reaction is 30h, the time of the third reaction is 30h, and the time of the fourth reaction is 10h, that is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=27.27%, and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=30% (greater than 15%); other conditions remain unchanged.
[0166] After testing, the particle size of the hydroxide precursor of Comparative Example 4 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 to 36.81%, the average hollow thickness of the cavity accounts for D2 to 12.41%, and after applying a pressure of 3.5T, ΔD50 is 7.46%.
[0167] Comparative Example 5
[0168] This comparative example is basically the same as Example 1, except that:
[0169] The time of the first reaction is 50h, the time of the second reaction is 10h, the time of the third reaction is 10h, and the time of the fourth reaction is 40h. That is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=45.45% (greater than 40%), and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=9.09%; other conditions remain unchanged.
[0170] After testing, the particle size of the hydroxide precursor of Comparative Example 5 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 9.79%, the average hollow thickness of the cavity accounts for D2 of 22.42%, and after applying a pressure of 3.5T, ΔD50 is 6.98%.
[0171] Comparative Example 6
[0172] This comparative example is basically the same as Example 1, except that:
[0173] The time of the first reaction is 12h, the time of the second reaction is 48h, the time of the third reaction is 10h, and the time of the fourth reaction is 40h. That is, the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3=10.9 (less than 15%), and the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4=9.09%; other conditions remain unchanged.
[0174] After testing, the particle size of the hydroxide precursor of Comparative Example 6 is 13.5μm, the D50 of the positive electrode active material is 13.0μm, the average hollow thickness of the second layer accounts for D1 of 10.27%, the average hollow thickness of the cavity accounts for D2 of 5.78%, and after applying a pressure of 3.5T, ΔD50 is 3.79%.
[0175] Test Example 1
[0176] The following parameters of the positive electrode active materials of the above embodiments and comparative examples were tested:
[0177] 1) Particle size of hydroxide precursor and D50 of positive electrode active material: tested using Malvern MasterSize 3000 particle size analyzer.
[0178] 2) The average hollow thickness of the second layer accounts for D1, and the average hollow thickness of the cavity accounts for D2: D1 = (r2-r3) / r1, D2 = r4 / r1, r1 is the D50 of the positive electrode particle, and the measurements of r2, r3, and r4 are as follows. Taking r2 as an example, take a cross-sectional SEM image of the positive electrode particle, such as Figure 3 , randomly select a point on the outer edge of the second layer (20) through the center of the particle to the outer edge of the other end of the layer as a sample point, and select at least 10 points. The software automatically calculates the average particle size, which is the r2 value. r3 and r4 are measured according to the above method.
[0179] 3) ΔD50: ΔD50 = (D50 压前 -D50 压后 ) / D50 压前 , D50 压前 Represents the D50 of the positive electrode active material, D50 压后 Represents the D50 result after testing at 3.5T pressure.
[0180] 3) Scanning electron microscope (SEM) images of the hydroxide precursor and the positive electrode active material of Example 1 and the scanning electron microscope (SEM) images of the positive electrode active material and of Comparative Example 1: see respectively Figure 2 , Figure 3 , Figure 4 .
[0181] Test results
[0182] Table 1
[0183]
[0184]
[0185] Data analysis: The average hollow thickness proportion D1 of the second ring layer and the average hollow thickness proportion D2 of the cavity of the positive electrode active material of the above-mentioned embodiments meet 0<D1≤16%, 10%≤D2≤20%, and ΔD50 is less than or equal to 5%. Compared with the embodiments, the outer layer of the positive electrode active material of comparative example 1 does not have a hollow structure, and its structural stability is poor, with a ΔD50 of 6.93%; the average hollow thickness of the outer layer of the positive electrode active material of comparative example 4 is too large, which is not conducive to maintaining its structural stability, with a ΔD50 of 7.46%; the average hollow thickness of the inner layer of the positive electrode active material of comparative example 5 is too large, which is not conducive to maintaining its structural stability, with a ΔD50 of 6.98%.
[0186] Test Example 2
[0187] After the positive electrode active materials of the embodiment and the comparative example are made into positive electrode sheets, they are assembled with negative electrode sheets, electrolytes and separators according to the following method to obtain 800mAh soft-pack batteries. The method includes:
[0188] The positive electrode active material, conductive agent Super-P and binder PVDF are mixed in a mass ratio of 90:5:5, and an appropriate amount of NMP solution is added to form a slurry. The mixed slurry is then coated on a positive electrode collector made of aluminum foil, dried and baked in a vacuum oven at 120°C for 12 hours to obtain a positive electrode sheet. Finally, the positive electrode sheet, negative electrode sheet (artificial graphite), separator (PP / PE / PP), and electrolyte (1.0MLiPF6 EC / DMC (1:1 volume ratio) solution) are assembled to obtain an 800mAh soft-pack battery.
[0189] The first coulombic efficiency (first efficiency), rate performance, impedance, and room temperature cycle performance of each soft-pack battery are tested. The specific testing methods are as follows:
[0190] First coulomb efficiency (first efficiency): At room temperature 25°C, charge the battery to 4.35V at a rate of 0.1C to obtain the charge capacity C 0.1 , and then discharge at a rate of 0.1C to 2.8V to obtain the discharge specific capacity D 0.1 , calculate D 0.1 / C 0.1 , get the first coulomb efficiency;
[0191] Rate performance: At room temperature 25°C, the battery is charged to 4.35V at 0.05C rate, and then discharged to 2.8V at the same rate to obtain the discharge specific capacity D at 0.05C. 0.05 , then charge to 4.35V at 0.33C, and then discharge to 2.8V at the same rate to obtain the discharge capacity D at 0.33C 0.33 , calculate D 0.33 / D 0.05 Get rate performance;
[0192] Impedance: At room temperature 25°C, charge the battery to 4.35V at 1C rate, then discharge it to 50% SOC at 1C rate, let it stand for 1h, record the voltage at this time as V1, then discharge it at 5C rate for 10s, record the voltage at this time as V2, and calculate the impedance as (V1-V2) / 4;
[0193] Normal temperature cycle performance: At room temperature 25°C, the battery is charged to 4.35V at a rate of 1C, and then discharged to 2.8V at a rate of 1C to obtain the first cycle discharge capacity D1. After 100 cycles according to this system, the 100th discharge capacity D 100 , calculate D100 / D1 gets the cycle retention rate.
[0194] Test results
[0195] Table 2
[0196]
[0197] It can be seen that the positive electrode active material of the embodiment of the present invention helps to improve the first coulombic efficiency and cycle performance. In addition, this structure of the above-mentioned positive electrode active material is also conducive to the full contact between the positive electrode active material and the electrolyte, thereby improving the conduction rate of lithium ions, helping to reduce impedance and improve rate performance.
[0198] Compared with the embodiments, Comparative Examples 1 and 3 do not have an outer hollow structure, and the average hollow thickness of the inner layer of Comparative Examples 2 and 6 is smaller. During the charge and discharge process, the stress may be released unevenly, resulting in damage to the structure and poor electrical performance; the average hollow thickness of the outer layer of Comparative Example 4 is too large, and the average hollow thickness of the inner layer of Comparative Example 5 is too large, and its cycle performance is poor. The thickness of the hollow layer is too large. During the charge and discharge process, excessive infiltration of electrolyte may cause more side reactions, resulting in serious irreversible phase changes, and further resulting in poor rate and impedance.
[0199] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes an inner layer and an outer layer in the radial direction from the inside to the outside, wherein the inner layer includes a third layer surrounding a cavity, and the outer layer includes a second layer located on a side of the third layer away from the cavity, and a first layer located on a side of the second layer away from the third layer; The positive electrode active material is composed of primary particles, and the second layer is a hollow structure including the primary particles; Along the radial direction from the inside to the outside, the radius of the positive electrode active material is r1, the width of the second layer is r2-r3, the width of the cavity is r4, the average hollow thickness of the second layer accounts for D1=(r2-r3) / r1, the average hollow thickness of the cavity accounts for D2=r4 / r1, D1 and D2 satisfy 0<D1≤16%, 10%≤D2≤20%.
2. The positive electrode active material according to claim 1, characterized in that The primary particles are not included in the cavity.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The change rate of D50 of the positive electrode active material after being kept at a pressure of 3.0-3.5T for 30s is less than or equal to 5%.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The chemical formula of the positive electrode active material is Li x Ni a Co b M c N e A f O2, wherein 0.95≤x≤1.1, 0.5≤a<1, 0≤b≤0.2, 0≤c≤0.5, a+b+c+e=1, 0<e≤0.01, 0<f≤0.01, M includes Mn and / or Al, N includes one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al, and A includes one or more of Al, W, Ti and Zr; And / or, the D50 of the positive electrode active material is 10 to 18 μm.
5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: include: 1) mixing a metal salt solution including nickel, cobalt and manganese, sodium hydroxide and ammonia water to obtain a mixed solution, wherein the pH of the mixed solution is 11.0 to 12.3 and the ammonia concentration is 2 to 15 g / L, subjecting the mixed solution to a first reaction to obtain a first mixed system, then lowering the pH of the first mixed system, increasing the ammonia concentration in the first mixed system, and subjecting the mixed solution to a second reaction to obtain a second mixed system; 2) adjusting the pH of the second mixed system to 10.5-11.5 and the ammonia concentration to 2-8 g / L, performing a third reaction to obtain a third mixed system, and then increasing the ammonia concentration in the third mixed system to perform a fourth reaction to obtain a hydroxide precursor; wherein the ratio of the time of the first reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D3, the ratio of the time of the third reaction to the sum of the time of the first reaction, the second reaction, the third reaction, and the fourth reaction is D4, and D3 and D4 satisfy 15%<D3≤40%, 2.5%≤D4≤15%; 3) mixing the hydroxide precursor and a raw material system including a lithium salt to obtain a mixed material; 4) performing a first sintering of the mixed material at 300-650° C., and then cooling to 20-25° C. to obtain the pre-lithiated lithium nickel cobalt manganese oxide; 5) The pre-lithiated lithium nickel cobalt manganese oxide is subjected to a second sintering at 550-750° C., then heated to 850-950° C. for a third sintering, and then subjected to a fourth sintering at 780-880° C. to obtain the positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
6. The preparation method according to claim 5, characterized in that: The temperature of the first reaction is 50-75°C; And / or, the temperature of the second reaction is 50-75°C; And / or, the temperature of the third reaction is 50-75°C; And / or, the temperature of the fourth reaction is 50-75°C; And / or, in step 1), the first reaction and the second reaction are carried out under stirring at a rotation speed of 300 rpm to 500 rpm; And / or, in step 2), the third reaction and the fourth reaction are carried out under stirring at a rotation speed of 100 rpm to 400 rpm; The raw material system in step 3) further includes a doping element, wherein the doping element includes one or more of Nb, Ti, Sr, Sb, Y, Mg, W, Mo, Zr and Al; And / or, the first sintering time is 4 to 15 hours; And / or, the second sintering time is 2 to 4 hours; And / or, the third sintering time is 8 to 15 hours; And / or, the fourth sintering time is 3 to 5 hours.
7. The preparation method according to claim 5 or 6, characterized in that: Also includes: The positive electrode active material is crushed, and then mixed with the coating material, and then a fifth sintering is performed at 300 to 700° C. to obtain a coated positive electrode active material. Wherein, the fifth sintering time is 5 to 12 hours.
8. The preparation method according to any one of claims 5 to 7, characterized in that: Step 4) comprises: heating the mixed material to 300-650° C. at a rate of 1-5° C. / min for a first sintering, and then cooling to 20-25° C. to obtain the pre-lithiated lithium nickel cobalt manganese oxide; And / or, step 5) comprises: heating the pre-lithiated lithium nickel cobalt manganese oxide to 550-750°C at a rate of 1-5°C / min for a second sintering, then heating it to 850-950°C at a rate of 1-3°C / min for a third sintering, then cooling it at a rate of 1-3°C / min, and performing a fourth sintering at 780-880°C to obtain the positive electrode active material, wherein the temperature of the fourth sintering is lower than the temperature of the third sintering.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material obtained by the preparation method according to any one of claims 5 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Ternary positive electrode material and preparation method thereof
CN112909260A
Ternary precursor, preparation method thereof and positive electrode material
CN116002776A
Positive electrode material precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment
CN117430170A
Positive electrode active material for nonaqueous secondary batteries, method for producing same, and nonaqueous electrolyte secondary battery using positive electrode active material
US20140087263A1
Positive electrode active material for non-aqueous electrolyte secondary batteries, production process therefor, and non-aqueous electrolyte secondary battery
US20170263930A1